# If f(x) = 2x^{2 }+ 3x and g(x) = x - 2, what is (f + g)(2)?

**Solution:**

It is given that,

function f(x) = 2x^{2 }+ 3x

g(x) =x - 2

(f +g)(x) means "add f(x) + g(x) together",

Here that would give: 2x^{2} + 3x + (x - 2) = 2x^{2} + 4x - 2

So (f + g)(2),

Now replace x by 2, and get the answer,

Then, 2(2)^{2} + 4(2) - 2 = 14

Therefore, (f + g)(2) is 14.

## If f(x) = 2x^{2 }+ 3x and g(x) = x - 2, what is (f + g)(2)?

**Summary:**

If f(x) = 2x^{2} + 3x and g(x) = x - 2, (f + g)(2) is 14.

Math worksheets and

visual curriculum

visual curriculum